Intracavitary Chemotherapy after kidney-Sparing Therapy for Upper Tract Urothelial Carcinoma: A Meta-Analysis - Zhou, Hang; Pan, Yang; Xu, Mingming; Wang, Shangren; Li, Yuezheng; Liu, Xiaoqiang (Urology Journal, 2023)
Purpose: Intracavitary chemotherapy is one of the current treatment options for kidney-sparing treatment of upper tract urothelial carcinoma (UTUC). The purpose of this meta-analysis was to assess the efficacy and safety of intracavitary perfusion. Methods: We carefully selected publications for study from four databases (Embase, PubMed, Web of Science, and Scopus) up to January 2023. The R 4.0.4 software was used to calculate the pooled ratio and its 95% confidence intervals (95% CIs). The I2 score was used to test heterogeneity, and the funnel plot was used to estimate the publication bias. Results: Thirty-four studies with a total of 788 patients were included in this study. The overall survival at a median follow-up of 26.3 months was 87.2% (95% CI 0.80–0.93). The cancer-specific survival at a median follow-up of 30 months was 94.1% (95% CI 0.89–0.98). At a median follow-up of 30 months, the recurrence rate of UTUC was 27.5% (95% CI 0.21–0.34). By subgroup analysis, we found that the recurrence rate in patients with T1 / Ta stage was 35.1% and CIS stage 29.0%. The recurrence rates of BCG, Mitomycin C, and Mitomycin Gel (UGN101) were 31.2%, 41.3% and 12.9%, respectively. The recurrence rates for anterograde and retrograde perfusion were 28.5% and 21.8%, respectively. Conclusion: With the advent of new drugs, including UGN101, patients with UTUC have a better prognosis. Therefore, kidney preservation therapy for patients with UTUC would be promising.